Respuesta :

It's not possible.

Thus, either use the Quadratic Formula, or look for a new method to find the solution.

Quadratic Formula:

[tex]x= \frac{-b(+/-) \sqrt{b ^{2} }-4ac }{2a} [/tex].
xy=1044
x+y=7

y=7-x
sub
x(7-x)=1044
7x-x^2=1044
0=x^2-7x+1044
use quadratice equaiton which is if you have
ax^2+bx+c=0 then
x=[tex] \frac{-b+/- \sqrt{b^{2}-4ac} }{2a} [/tex]

ax^2+bx+c=0
1x^2-7x+1044=0
a=1
b-7
c=1044

x=[tex] \frac{-(-7)+/- \sqrt{(-7)^{2}-4(1)(1044)} }{2(1)} [/tex]
x=[tex] \frac{7+/- \sqrt{49-4176} }{2} [/tex]
x=[tex] \frac{7+/- \sqrt{-4127} }{2} [/tex]
x=[tex] \frac{7+/- \sqrt{-4127} }{2} [/tex]
aprox
x=-3.5+32.120865492698i or
-3.5- 32.120865492698i 
where i=√-1


so the numbers are -3.5+32.120865492698i and
-3.5- 32.120865492698i 
where i=√-1